Monte Carlo simulations of the electron short-range quantum ordering in Coulomb systems and the 'fermionic sign problem'. (23rd December 2021) - Filinov, V; Levashov, P; Larkin, A
Abstract: To account for the interference effects of the Coulomb and exchange interactions of electrons the new path integral representation of the density matrix has been developed in the canonical ensemble at finite temperatures. The developed representation allows to reduce the notorious 'fermionic sign problem' in the path integral Monte Carlo simulations of fermionic systems. The obtained results for pair distribution functions in plasma and uniform electron gas demonstrate the short-range quantum ordering of electrons associated in literature with exchange-correlation excitons. The charge estimations show the excitonic electric neutrality. Comparison of the internal energy with available ones in the literature demonstrates that the short range ordering does not give noticeable contributions to integral thermodynamic characteristics. This fine physical effect was not observed earlier in the standard path integral Monte Carlo simulations.